Calibration, event reconstruction, data analysis, and limit calculation for the LUX dark matter experiment - Akerib,DS; Alsum,S; Araujo,HM; Bai,X; Bailey,AJ; Balajthy,J; Beltrame,P; Bernard,EP; Bernstein,A; Biesiadzinski,TP; Boulton,EM; Bras,P; et al. (PHYSICAL REVIEW D, 2018)
The LUX experiment has performed searches for dark-matter particles scattering elastically on xenon nuclei, leading to stringent upper limits on the nuclear scattering cross sections for dark matter. Here, for results derived from 1.4×104  kg days of target exposure in 2013, details of the calibration, event-reconstruction, modeling, and statistical tests that underlie the results are presented. Detector performance is characterized, including measured efficiencies, stability of response, position resolution, and discrimination between electron- and nuclear-recoil populations. Models are developed for the drift field, optical properties, background populations, the electron- and nuclear-recoil responses, and the absolute rate of low-energy background events. Innovations in the analysis include in situ measurement of the photomultipliers’ response to xenon scintillation photons, verification of fiducial mass with a low-energy internal calibration source, and new empirical models for low-energy signal yield based on large-sample, in situ calibrations.